PERANCANGAN COLLABORATIVE PLANNING FORECASTING REPLENISHMENT “TRAVEL BAG” PADA TRAVEL AGENT DWIDAYA TOUR - Erwin Ramdhanu Kurniawan; Sawarni Hasibuan (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
Travel bag for the tourism industry was a gift from tour product that was sold at travel agents in the tourism industry. Some of the conditions faced by customers who are departing tour travel bag are not given due to delays in fulfillment and delivery. This has led to poor ratings from customers and received several other losses such as lack of promotion, and testimonials from customers that are less good. With an action research methods of collaborative planning forecasting replenishment of supported data and processing that also use the quantitative forecasting models and assisted reorder point so that it can present the data to be analyzed. From the analysis obtained forecasting models that fit or in accordance with the collaborative planning forecasting replenishment study is the model Multiplicative Decomposition (plus Seasonal Trend), which is then used for process planning, forecasting and reorder point or ROP for replenishment process. Apart from that there is web-based application that is used for collaborative processes. From this action research concluded that collaborative planning forecasting replenishment, forecasting models Multiplicative Decomposition (plus Seasonal Trend), ROP, and collaboration could be a solution to the existing problems and achieve the desired objectives.